1996
DOI: 10.1111/j.1469-8137.1996.tb04508.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and sugar accumulation in durum wheat plants under water stress

Abstract: SUMMARYThe effect of water stress on growth of Triticum durum L, was in\estigated in relation to sugar accumulation and water status ot wheat plants before, during and after a ptriud of water stress. The slight decrease in water potential in the first few days after withholding water had no detectable efTect on growth. Inhibition of growth was only apparent when the water content started to decline. Dry weight continued to increase during water stress, even under severe stress (after day 27) which was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 36 publications
(40 reference statements)
5
26
0
Order By: Relevance
“…These results are in accordance with the findings of Mohammadkhani and Heidari (2008), Tatar and Gevrek (2008) and Kameli and Losel (1996) who reported that wheat sugar and proline content increased under drought stress conditions. Higher proline content in wheat plants after water stress has also been reported by Vendruscolo et al (2007) and Patel and Vora (1985).…”
Section: Resultssupporting
confidence: 93%
“…These results are in accordance with the findings of Mohammadkhani and Heidari (2008), Tatar and Gevrek (2008) and Kameli and Losel (1996) who reported that wheat sugar and proline content increased under drought stress conditions. Higher proline content in wheat plants after water stress has also been reported by Vendruscolo et al (2007) and Patel and Vora (1985).…”
Section: Resultssupporting
confidence: 93%
“…Sugar accumulation is a response phenomenon under different stresses, such as cold stress (Malone et al 2006), osmotic and salinity stress (Watanabe et al 2012), and water stress (Kameli and Lösel 1996). This may related to the fact that the sugars are effective in the regulation of osmotic pressure in plant cells.…”
Section: Expressions Of Sugar Metabolism Related Genesmentioning
confidence: 99%
“…The increase of sugar in various plant tissues response to water stress are supported the idea of contribution of solutes while the plants exposed to different stress levels. The studies have shown that soluble sugars accumulate in leaves during water stress [60,71,79,[87][88][89][90], and have suggested that these sugars might contribute to osmoregulation [65], at least under moderate stress. Quick et al, (1992) [60] compared the effect of water stress on the rate of photosynthesis and the partitioning of photosynthate in four different species, including two annuals (Lupinus albus L. and Helianthus annuus L.), and two woody perennials (Vitis vinifera cv.…”
Section: Carbohydrates Changes Under Water Stressmentioning
confidence: 99%